2020
DOI: 10.3389/fonc.2020.570281
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Metabolic-Genes Risk Score Model Predicts Overall Survival in Clear Cell Renal Cell Carcinoma Patients

Abstract: Metabolic alterations play crucial roles in carcinogenesis, tumor progression, and prognosis in clear cell renal cell carcinoma (ccRCC). A risk score (RS) model for ccRCC consisting of disease-associated metabolic genes remains unidentified. Here, we utilized gene set enrichment analysis to analyze expression data from normal and tumor groups from the cancer genome atlas. Out of 70 KEGG metabolic pathways, we found seven and two pathways to be significantly enriched in our normal and tumor groups, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Beta-1,3-glucuronyltransferase 3, encoded by the B3GAT3 gene, is crucial for proteoglycan (PG) biosynthesis [ 38 ]. Since PG could affect the cell cycle and was related to tumor cell invasion and metastasis [ 39 , 40 ], the potential role of B3GAT3 in tumor development, progression and prognosis was explored [ 41 ]. Recently, Zhang et al [ 42 ] found that B3GAT3 was upregulated in HCC samples, and the dysregulation of B3GAT3 was associated with poorer pathological characteristics, tumor invasion, migration and a more adverse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Beta-1,3-glucuronyltransferase 3, encoded by the B3GAT3 gene, is crucial for proteoglycan (PG) biosynthesis [ 38 ]. Since PG could affect the cell cycle and was related to tumor cell invasion and metastasis [ 39 , 40 ], the potential role of B3GAT3 in tumor development, progression and prognosis was explored [ 41 ]. Recently, Zhang et al [ 42 ] found that B3GAT3 was upregulated in HCC samples, and the dysregulation of B3GAT3 was associated with poorer pathological characteristics, tumor invasion, migration and a more adverse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of this study revealed that low expression of PTRPG could predict poor prognosis. According to recent reports, other genes, such as MID1IP1 (30), ABCD1 (31), CPT2 (32), and TP53INP2 (33), are closely associated with the progression of ccRCC. However, our study is the first to demonstrate that FAAH2 is inhibited in ccRCC and is an indicator of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…B3GAT3 participates in the biosynthesis of the glycosaminoglycan (GAG) linker region of proteoglycan (PG) ( BarrĂ©, et al, 2006 ). Given its important role in tumour metabolism, which was used repeatedly as a candidate gene for constructing prognostic models ( Zhao, et al, 2021 ; Zhao, et al, 2020 ; Bingxiang, et al, 2021 ), its function of promoting the process of tumour EMT in HCC was confirmed by experimental verification ( Zhang, et al, 2019 ). Based on the analysis above, the cancer-promoting effects of dysregulated expression are in accordance with our prediction results.…”
Section: Discussionmentioning
confidence: 99%